Demographics of Fall-Related trauma among the Elderly Presenting to Emergency Department; a Cross-Sectional Study - Morteza Bagi, Hamid Reza; Ahmadi, Sajjad; Hosseini, Maryam (Archives of Academic Emergency Medicine, 2017)
Introduction: Falling is reported to be the most common cause of mortality due to trauma in individuals over the age of 75 years. The present study is designed with the aim of determining the demographics of fall-related trauma among the elderly presenting to emergency department (ED). Methods: The present prospective cross-sectional study was carried out on all elderly patients ≥ 60 years old presenting to ED of a major referral trauma center in North West of Iran during 1 year. Demographic data, location and height of falling, duration of hospitalization, trauma severity and in-hospital outcome of the patients were gathered and reported via descriptive statistics. Results: 228 patients with the mean age of 70.96 ± 5.2 years were studied (53.9% female). Most patients were in the 66-70 years age range (32.6%) and had a history of hypertension (22.3%), who had visited following a fall inside the house (69.3%), due to slipping (73.7%), and from a height equal to or less than 2m (71.9%). 6 (2.6%) patients died in the hospital. Mean trauma severity of patients based on ISS, RTS, and TRISS were 10.65 ± 3.95 (3-19), 7.84 ±.21 (1.4-14.5) and 1.66 ±1.31 (-1.49-3.82), respectively. Regarding need for hospitalization, only ISS shows a significant difference between outpatients and inpatients (p = 0.023). Patients who died had a significantly higher trauma severity based on ISS (p < 0.0001) and RTS (p < 0.0001). Conclusion: Based on the findings of the present study, slipping and syncope are the most common causes of falling in the studied elderly that had mostly happened inside the house and from a height less than 2m. Therefore, most patients were in the mild to moderate range of trauma severity. ISS and RTS were significantly higher in the 6 (2.6%) patients who died.